Reconstruction of the anterior cruciate ligament with quadriceps tendon. - NORONHA, J.C. (2010)
We found 1 article: Arthroscopy. 2002 Sep;18(7):E37. Reconstruction of the anterior cruciate ligament with quadriceps tendon. Noronha JC. Department of Trauma and Orthopaedic Surgery, Hospital Santo António, Porto, Portugal. noronha@mac.com Abstract The author describes the technique he uses to reconstruct the anterior cruciate ligament (ACL) arthroscopically with autologous bone-quadriceps tendon (BQT) graft. The patellar bone is fixed in a femoral tunnel about 2.5 cm long, in a position that allows the tendinous extremity of the graft to appear on the extra-articular exit of the tibial tunnel. The tibial tunnel is filled, making the integration of the tendon in the bone easier. The tendinous extremity of the graft is pulled by nonabsorbable wires, remaining strictly fixed by a staple or a screw in the anterointernal cortex of the tibia. When used in selected cases and when technical details are respected, this technique yields results similar to those obtained with the bone-patella tendon-bone (BPTB) graft. The functional recovery should be more careful with this technique than when the BPTB is used. Generally, less morbidity is seen with the BQT graft. The author believes that the BQT graft will be used more frequently, especially in ACL reconstruction, for patients whose jobs require kneeling or long periods of knee flexion, or in cases of low patella, patellar chondropathy, or tendinopathy of the patellar tendon. This technique may also be appropriate for revision surgeries. PMID: 12209422 [PubMed - indexed for MEDLINE]